Asymmetric transfer hydrogenation of imines in water by varying the ratio of formic acid to triethylamine - Shende, Vaishali S.; Deshpande, Sudhindra H.; Shingote, Savita K.; Joseph, Anu; Kelkar, Ashutosh A. (Organic Letters, 2015)
Asymmetric transfer hydrogenation (ATH) of imines has been performed with variation in formic acid (F) and triethylamine (T) molar ratios in water. The F/T ratio is shown to affect both the reduction rate and enantioselectivity, with the optimum ratio being 1.1 in the ATH of imines with the Rh-(1S,2S)-TsDPEN catalyst. Use of methanol as a cosolvent enhanced reduction activity. A variety of imine substrates have been reduced, affording high yields (94-98%) and good to excellent enantioselectivities (89-98%). In comparison with the common azeotropic F-T system, the reduction with 1.1/1 F/T is faster.